Nurses experiences regarding ideal clinic project implementation in eThekwini district - Thembelihle S.P. Ngxongo; Mthokozisi Zulu (AOSIS, 2024)
Background: The South African National Department of Health introduced the ideal clinic realisation and maintenance (ICRM) programme in response to primary health care (PHC) services and to lay a strong foundation for the National Health Insurance implementation. The progress report 2015-2016 on the implementation of this programme indicated that achieving the 50% target in selected vital areas such as staffing, resource allocation, and utilisation was not achieved. Aim: The study aimed to explore and describe nurses' experiences regarding the ideal clinic project (ICP) implementation. Setting: The study was conducted in 18 PHC clinics in eThekwini district, KwaZulu-Natal. Methods: An exploratory descriptive, contextual qualitative design was employed guided by Donabedian's structure, process, and outcomes model. Data were collected using semi-structured interviews with 24 nurses between 15 September and 25 October 2020 following receipt of ethics and analysed using Tesch's open coding approach. Results: The three themes that emerged included structural limitations, processes involved in running the clinic, and support offered to the PHC clinics. These were highlighted as challenges experienced by nurses during the implementation of an ICP. Conclusion: Nurses' negative experiences and perceptions made it difficult for them to accomplish the ICP standards. Contribution: The findings from the study highlighted critical actions by the health care institution management which if instituted, could facilitate improved implementation of the ICP and achievement of the 50% target in selected vital areas.